Pemantauan Tumbuh Kembang Balita di Posyandu Berbasis Web dengan WhatsApp Api - Andrian Rizka Ramadhan, Andrian Rizka Ramadhan; Tri Listyorini, Tri Listyorini; Endang Supriyati, Endang Supriyati (Yayasan Literasi Sains Indonesia, 2022)
The implementation of the Integrated Service Post or better known as Posyandu uses a manual method by collecting data using books. This manual data collection can result in invalid data, delays in making reports on the results of Posyandu activities both by Posyandu itself and related agencies such as Puskesmas and Kelurahan. Due to the lack of information provided, there is also a lack of community participation. To overcome the problems that arise, the Posyandu Information System Web is made to connect with the WhatsApp API. The WhatsApp API is expected to help convey information to the public through broadcast messages sent by the local Posyandu. System development follows the waterfall method and system design uses UML (Unified Modeling Language). The results of this study resulted in the design and creation of a website that can manage Posyandu data, convey Posyandu information messages and to make it easier for parents to monitor their baby's growth and development